ANALISIS PEMBELAJARAN BERBASIS MASALAH DALAM PERSEPEKTIF FILSAFAT PROGRESIVISME - Sholeh, Abdus; Mochamad Nursalim; Andi Kristanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Problem-based learning is a learning model that focuses on students so that they are required to be able to solve learning problems independently and collaboratively. Learning that can solve problems with creativity and critical thinking so that students can gain the ability to find solutions that are relevant to the learning problems faced by students. The philosophy of progressivism is the basis of the problem-based learning model because the pressure of the learning experience given gives the impression that learning is meaningful and enjoyable. Philosophically, progressivism implies that teachers as facilitators are not the only source of learning. However, students' success in solving learning problems cannot be separated from the role of a teacher. This means that the problem-based learning model and the progressivism perspective are a relevant and integrated view of learning concepts. The aim of this research is to examine the relevance of the concept of problem-based learning to the philosophical perspective of progressivism. The research method uses literature views that are described qualitatively. Data obtained from various scientific journals, books and studies that are relevant to the same concept of point of view. The conclusion from the perspective of the concept of problem-based learning with the perspective of the progressivism school of education is that there is an interconnectedness in the existence of theoretical and practical learning.